Usinas hidrelétricas no rio Paraná : insustentabilidade e exclusão social em populações tradicionais de Ituzaingó (Corrientes, Argentina) e Porto Rico (Paraná, Brasil). - Ulloa Campos, Víctor Manuel (2006)
The promotion of mega-constructions, as reservoirs of Itaipu and Yacyretá, are based in ideas of development and progress. However, the report showed by the World Commission on Dams (WCD) in November of 2000, made responsible to the big reservoirs, the projects on Sustainable Regional Development (SRD), as generating of social and environmental damages. Thus, the main goal of the present study is to investigate the social and cultural transformations in the communities of the islanders and riparian people from Ituzaingó and Porto Rico with the constructions of the hydroelectric power plants of Itaipu (Brazil), Porto Primavera (Brazil) and Yacyretá (Argentina). Are analyzed many factors that allowed the built of those reservoirs and their principal actors. Also, the contradictions more visible verified in the social community and environmental of Ituzaingó and Porto Rico. The three reservoirs are located on the Paraná River basin, because the exploration of there hidroelectrical potential and promote of development of the different regions. Although, the reservoirs of Itaipu and Yacyretá, as projects of DRS, not allowed better social conditions for the traditional communities of Porto Rico and Ituzaingó, and they were made loose their significance when they are compare with the damages caused. In the other hand, its main beneficiaries are the multilateral financiers agencies and the economical trusts with distant headquarters from the south of Brazil and the northeast of Argentina